Dementia and Mental Health During the COVID-19 Pandemic: A Systematic Review - Gaigher, Julia Mariano; Lacerda, Isabel Barbeito; Dourado, Marcia Cristina Nascimento (Frontiers in Psychiatry, 2022)
Objectives The COVID-19 pandemic raised significant concerns related to the management of care for people with dementia, but few studies have examined the mental health of older adults with dementia and their caregivers during the pandemic, when compared to other populations. This systematic review thus aims to compare and discuss the impact of the COVID-19 pandemic on people with dementia and on their caregivers' mental health. Methods A search was performed in the PubMed/Medline and ISI databases according to the PRISMA methodology. We included studies published in 2020 and 2021 with the following combinations of keywords: “COVID-19 and mental health and elderly,” “COVID-19 and mental health and dementia;” “COVID-19 and dementia and caregivers,” “pandemic and mental health and elderly,” and “pandemic and anxiety.” Results Twenty-two studies were included. Technology has proven to be an essential ally during the pandemic, since all 22 studies performed remote data collection. Nearly all the studies emphasized that social isolation and withdrawal can lead to the emergence or increase of neuropsychiatric symptoms and motor difficulties. However, the findings were mixed concerning the pandemic's impact on the cognition of people with dementia. Caregivers also suffered from the pandemic's impact, experiencing an increase in the burden of care and symptoms of stress, depression, and anxiety. Few studies suggested measures to alleviate the difficulties of people with dementia and their caregivers. There are reports of the benefits of technology in communication and treatment through teleconsultations, however, not everyone has access to such technology, making it difficult to disseminate this tool to the target population. Conclusions The studies generally showed that social isolation can increase motor deficits and neuropsychiatric symptoms and caregivers' burden and anxiety. New avenues for care and intervention are thus needed for older adults with cognitive deficits and their caregivers to avoid the intensification of physical and psychological suffering. Technological initiatives and support should consider people with cognitive impairment and different levels of technology literacy. Systematic Review Registration https://www.crd.york.ac.uk/prospero/.